Hermeneutics of the judicial text: A construction based on Paul Ricoeur [Hermenéutica del texto judicial: Una construcción desde Paul Ricoeur] (2020)
"The aim of this paper is to propose a hermeneutics of the judicial text based on Paul Ricoeur's philosophy. For this purpose, the paper will propose, firstly, how to approach the judicial decision as text; secondly, the paper will argue from Paul Ricoeur's notion of ""Hermeneutic Arc,"" how explanation and understanding as a hermeneutic method are given in the judicial decision. The final purpose is to show how in some cases the comprehension of ourselves could go through the hermeneutics made to the judicial text. © 2020 Universidad Panamericana. All rights reserved."